Implementasi Aplikasi Berbasis Teknologi IoT pada Perangkat Tracking dan Kendali Kendaraan Bermotor - Ade Irma; Martinus Mujur Rose; Nasron (Jurnal CoSciTech (Computer Science and Information Technology), 2020)
The increasing use of vehicles, especially motorbikes, has the potential to increase motor vehicle theft cases. The increase in motorcycle theft cases can occur due to the weakness of the owner in installing a motorcycle security system, so that it has the potential to experience losses due to theft. An indication of the problem is how to develop an application that can be used to carry out tracking that can display the position of the vehicle with integrated maps and vehicle control remotely in the event of a vehicle theft. The development of Internet of Things (IoT) technology as well as information and communication technology can now be used to develop an application for wireless vehicle monitoring and control. So that it can make it easier for vehicle owners to track and control the vehicle to minimize vehicle loss. In this study using MIT App Inventor as an application development platform and using ThingSpeak as an IoT database server. Furthermore, the application will be integrated with the Tracking Device device consisting of a microcontroller, Global Positioning System (GPS) module, and a DC relay installed on the vehicle, utilizing an internet connection as a link between the application and the tracking device. The result is that vehicle position data can be displayed through a mobile application with map visualization integrated with google maps and the user can turn off or turn on the vehicle through the application with the farthest distance that has been successfully tested of 141 km. The time for the tracking device to respond to commands from the application varies from 5 to 20 seconds depending on the strength of the internet connection used. Keywords : Internet of Things (IoT), Tracking Device, Global Positioning System (GPS), mikrokontroler.